Citizenship education beyond the rights (Andamios, Revista de Investigación Social, 2012)
In this article, I propose Axel Honneth´s concept of formal ethical life as a normative standpoint of a democratic ethos. Democratic societies are presented as postradicional communities because they integrate two fundamental spheres of recognition: respect and solidarity. From this, I suggest that the model of civic education for such type of community needs to be beyond a model based on rigths.
Keywords: Ethical life; democracy; Honneth; rights; solidarity